A qualitative feasibility study to inform a randomised controlled trial of fluid bolus therapy in septic shock. Issue 1 (28th August 2017) - O'Hara, Caitlin B; Canter, Ruth R; Mouncey, Paul R; Carter, Anjali; Jones, Nicola; Nadel, Simon; Peters, Mark J; Lyttle, Mark D; Harrison, David A; Rowan, Kathryn M; Inwald, David; Woolfall, Kerry
Abstract : Objective: The Fluids in Shock (FiSh) Trial proposes to evaluate whether restrictive fluid bolus therapy (10 mL/kg) is more beneficial than current recommended practice (20 mL/kg) in the resuscitation of children with septic shock in the UK. This qualitative feasibility study aimed to explore acceptability of the FiSh Trial, including research without prior consent (RWPC), potential barriers to recruitment and participant information for a pilot trial. Design: Qualitative interview study involving parents of children who had presented to a UK emergency department or been admitted to a paediatric intensive care unit with severe infection in the previous 3 years. Participants: Twenty-one parents (seven bereaved) were interviewed 16 (median) months since their child's hospital admission (range: 1–41). Results: All parents said they would have provided consent for the use of their child's data in the FiSh Trial. The majority were unfamiliar with RWPC, yet supported its use. Parents were initially concerned about the change from currently recommended treatment, yet were reassured by explanations of the current evidence base, fluid bolus therapy and monitoring procedures. Parents made recommendations about the timing of the research discussion and content of participant information. Bereaved parents stated that recruiters should not discuss research immediately after a child's death, but supported a personalised postal 'opt-out' approach to consent. Conclusions: Findings show that parents whose child has experienced severe infection supported the proposed FiSh Trial, including the use of RWPC. Parents' views informed the development of the pilot trial protocol and site staff training. Trial registration number: ISRCTN15244462 —results.